3.2-mJ sub-10-fs pulses at 100 kHz - Hädrich, Steffen; Simon, Peter; Nagy, Tamás; Blumenstein, Andreas; Walther, Nico; Kienel, Marco; Shestaev, Evgeny; Stutzki, Fabian; Gaida, Christian; Breitkopf, Sven; Jójárt, Péter; Várallyay, Zoltán; et al. (Optics InfoBase Conference Papers, 2019)
We present sub-10-fs, 3.2mJ pulses at 100kHz repetition-rate. This significant upscaling of average power was achieved by using a 6-m-long stretched flexible capillary. Such a technique has the potential to revolutionize few-cycle laser beamlines.
CRIS-Team Scopus Importer:2023-04-20